10 things you don't know about. (Academic Video Online, 2013)
In "10 Things You Don't Know About", punk rock icon Henry Rollins uncovers crazy twists and tidbits behind the historical tales, figures, and places you only thought you knew. Whether he's analyzing centuries-old documents at the National Archives or exploring the inside of a dead gangster's speakeasy, he's on a mission to discover the info every casual history fan needs to know. The White House might be the most recognizable home in the entire world. But as a Washington, D.C. native, Henry Rollins knows there's far more to 1600 Pennsylvania Avenue than meets the eye.